mCRP as a Biomarker of Adult-Onset Still’s Disease: Quantification of mCRP by ELISA - Fujita, Chitose; Sakurai, Yasuo; Yasuda, Yuki; Homma, Rino; Huang, Cheng-Long; Fujita, Masaaki (Frontiers in Immunology, 2022)
Background C-reactive protein (CRP) is a dynamic protein that undergoes conformational changes between circulating native pentameric CRP (pCRP), pentameric symmetrical forms (pCRP*) and monomeric (or modified) CRP (mCRP) forms. mCRP exhibits strong pro-inflammatory activity and activates platelets, leukocytes, and endothelial cells. Abundant deposition of mCRP in inflamed tissues plays a role in several disease conditions, such as ischemia/reperfusion injury, Alzheimer’s disease, and cardiovascular disease. Although pCRP is typically quantified rather than mCRP for clinical purposes, mCRP may be a more appropriate disease marker of inflammatory diseases. Therefore, simple methods for quantifying mCRP are needed. Methods We developed a specific enzyme-linked immunosorbent assay (ELISA) to measure plasma levels of mCRP. Plasma mCRP concentration was measured in patients with adult-onset Still’s disease (AOSD) (n=20), polymyalgia rheumatica (PMR) (n=20), rheumatoid arthritis (RA) (n=30), infection (n=50), and in control subjects (n=30) using the developed ELISA. Results We demonstrated that mCRP is elevated in some inflammatory autoimmune diseases, particularly AOSD. The mCRP concentration was also significantly higher among AOSD patients than RA, PMR patients and controls (477 ng/ml, 77 ng/ml, 186 ng/ml, and 1.2 ng/ml, respectively). Also, the mCRP (×1,000)/pCRP ratio was significantly higher among AOSD patients than RA, PMR, and infection patients (3.5, 0.6, 1,6, and 2.0, respectively). Conclusion The plasma mCRP levels are elevated in some autoimmune diseases, particularly AOSD. The plasma mCRP levels may therefore be a potentially useful biomarker for AOSD.